Research of Estimates of Tax Revenue: An Overview - Ondřej Bayer (European Financial and Accounting Journal, 2013)
The paper deals with a summary of findings in the area of tax forecasts. It describes the basic methodology for predicting tax revenues, both in terms of the macroeconomic approach and from a microeconomic perspective. The microeconomic approach used microsimulation methods with methods based on tax elasticities. The macroeconomic approach explains the basic characteristics of regression analysis and time series analysis. It also describes methods for assessing the quality of predictions, together with the distribution of basic statistical error estimate.
Keywords: H29; 650; Tax revenue; Forecasting; Microsimulations; Regression analysis